PENGARUH PENERAPAN MEDIA GEOLEGEND TERHADAP HASIL BELAJAR GEOGRAFI DI SMAN MODEL TERPADU BOJONEGORO - Listari, Tria; Lestari Sitohang, Lidya; Perdana Prasetya, Sukma; Murtini, Sri (Jurnal Pendidikan : Riset dan Konseptual, 2025)
Students' learning outcomes in geography class at Bojonegoro Integrated Model Senior High School are caused by their difficulty in understanding the concepts. Only 14 out of 34 students who took the daily test were complete and reached the KKM of around 75. This study aims to analyze the impact of GeoLegend learning media on geography learning outcomes. This study used pre-experimental design method with one group pre-test-post-test. The population of Bojonegoro Integrated Model Senior High School includes all grade X students. Purposive random sampling was used to select the sample, and the results showed that the sample could accurately represent the population, which included one class consisting of 36 students. The information provided was learning outcomes before and after the application of GeoLegend media. Data analysis used statistical tests, such as normality test, homogeneity, and T test. The results showed that there was a difference in the average before the application of 66.67 and after the application of 84.72. The highest pre-test score reached 80, while the lowest reached 40. The highest post-test score reached 100 and the lowest reached 60. There was an increase in the value of students who reached the KKM of almost 55% both before and after the launch of GeoLegend media.